Muscle delta C-13 change in Nile tilapia (Oreochromis niloticus): Effects of growth and carbon turnover - Zuanon, J. A. S.; Pezzato, Antonio Celso [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Passos, J. R. S.; Barros, Margarida Maria [UNESP]; Ducatti, Carlos [UNESP] (Elsevier B.V., 2006)
The contribution of growth and turnover to the muscle delta C-13 change process was investigated using mathematical models which associate delta C-13 change to time of intake of a new diet or increase in body mass. Two groups of Nile tilapia (Oreochromis niloticus) were fed on diets based on C3 (sigma C-13 = - 25.64 +/- 0.06 parts per thousand) or C4 (delta C-13= -16.01 +/- 0.06 parts per thousand) photosynthetic cycle plants to standardize the muscle delta C-13. After establishing the carbon isotopic equilibrium, fish (mean mass 24.12 +/- 6.79 g) then received the other treatment diet until a new carbon isotopic equilibrium could be established, characterizing T1 (C3-C4) and T2 (C4-C3) treatments. No significant differences were observed in fish productive performance. Good fits were obtained for the models that associated the delta C-13 change to time, resulting in carbon half-life values of 23.33 days for T1 and 25.96 days for T2. Based on values found for the muscle delta C-13 change rate from growth (0.0263 day(-1) and 0.0254 day(-1)) and turnover (0.0034 day(-1) and 0.0013 day(-1)), our results indicate that most of the delta C-13 change could be attributed to growth. The application of model that associated the delta C-13 change to body mass increase seems to produce results with no apparent biological explanation. The delta C-13 change rate could directly reflect the daily ration and growth rate, and consequently the isotopic change rates of carbon and other tissue elements can be properly used to assess different factors that may interfere in nutrient utilization and growth. (c) 2006 Published by Elsevier B.V.
Keywords: carbon; fish; growth; isotopic change rate; mathematical models; Nile tilapia; stable isotopes; turnover